Contextual Teaching Learning (CTL) Learning Model and Learning Motivation on the Ability of Writing Narrative Texts of Grade XII Students State Senior High School 1 Wanasari, Brebes District - Larastanti, Renastasya; Basuki, Basuki; Setiyadi, D.P Putut; Hersulastuti, Hersulastuti; Herawati, Nanik (Journal of English Language and Education, 2025)
The study aims to: 1. Determine the effect of the CTL learning model on the ability to write narrative texts, 2. Determine the effect of motivation on the ability to write narrative texts, and 3. Determine the effect of the CTL learning model and motivation on the ability to write narrative texts. The study was conducted using a descriptive correlative method, which explains the relationship between two or more variables. In this case, it is to explain the relationship between the CTL learning model and learning motivation on the ability to write narrative texts. The subjects of the study were grade XII students of SMA Negeri Wanasari Brebes in the 2023/2024 academic year. The study was conducted from September to December 2024. Samples were taken from 2 classes, 1 class as an experimental class and 1 control class. Samples were taken using a cluster random sample. Data were obtained through documentation, tests, and questionnaires. Data analysis was carried out using the multiple classification variance analysis formula technique. The results of the analysis are as follows: 1. The calculated F for the research group was 9.894 with a significance of 0.002 0.05. 2. F count for motivation is 8.060 with a significance of 0.001 0.05. 3. F count for the interaction of learning models and motivation is obtained at 3.462 with a significance of 0.03 0.0. From the significance value, it can be stated that Ho for the three hypotheses is rejected and Ha is accepted. Based on the hypothesis testing, it can be concluded that: 1. The CTL model has a significant effect on the ability to write narrative texts. 2. Learning motivation has a significant effect on the ability to write narrative texts. 3. The interaction between the CTL learning model and learning motivation has a significant effect on the ability to write narrative texts.